2008
DOI: 10.1103/physrevlett.101.076803
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Insulator Transition in an Aperiodic Ladder Network: An Exact Result

Abstract: We prove that a tight-binding ladder network composed of atomic sites with on-site potentials distributed according to the quasiperiodic Aubry model can exhibit a metal-insulator transition at multiple values of the Fermi energy. For specific values of the first and second neighbor electron hopping, the result is obtained exactly. With a more general model, we numerically calculate the two-terminal conductance. The numerical results corroborate the analytical findings.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
99
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 83 publications
(101 citation statements)
references
References 41 publications
1
99
1
Order By: Relevance
“…Sil et al have shown that a ladder network, consisting of two identical AA chains, exhibits an MIT at multiple Fermi energies in the presence of next-nearestneighbor (NNN) hopping. 21 Biddle et al have studied the localization properties of the AA chain by considering non-nearest-neighbor hopping and found the mobility edges.…”
Section: -14mentioning
confidence: 99%
“…Sil et al have shown that a ladder network, consisting of two identical AA chains, exhibits an MIT at multiple Fermi energies in the presence of next-nearestneighbor (NNN) hopping. 21 Biddle et al have studied the localization properties of the AA chain by considering non-nearest-neighbor hopping and found the mobility edges.…”
Section: -14mentioning
confidence: 99%
“…The metal-insulator (MI) transition is one of the most significant phenomena in condensed matter physics [1][2][3][4][5] . The usual band structure predictions are not capable of exploring many experimental evidences.…”
Section: Introductionmentioning
confidence: 99%
“…3(b) we obtain β=−1], due to the Anderson localization effects, although they possess either the diagonal disorder (dashed lines) or the off-diagonal disorder (dotted lines) and are more ordered than the former case. the disorder degree is very large [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33], we can see from Fig. 3(c) that ξ L is independent of W for the former ladder and all states are always extended in the gray energy region [ Fig.…”
mentioning
confidence: 99%